Inflammatory Response of Tumor Necrosis Factor-alpha (TNF-α) in Incised Wounds of White Rats (Rattus norvegicus) Induced by Aloe vera Extract - Pauzan, Pauzan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Incised wounds are common injuries that trigger an inflammatory response, in which Tumor Necrosis Factor-alpha (TNF-α) plays a crucial role in the pathogenesis. Aloe vera has long been recognized for its wound-healing potential; however, its molecular mechanisms particularly in modulating TNF-α expression remain incompletely understood. This study aims to investigate the effect of Aloe vera extract on TNF-α expression in incised wounds of white rats. This experimental study employed a controlled group design, involving a positive control group (K+), a negative control group (K−), and a treatment group (P), each consisting of five white rats. Incised wounds were created on the dorsum of the rats, and the treatment group received topical Aloe vera extract. TNF-α expression was evaluated using immunohistochemical methods on days 3, 7, and 14 post-wounding. The treatment group that received Aloe vera extract showed a significant decrease in TNF-α expression compared to the negative control group on days 7 and 14. Aloe vera extract modulates TNF-α expression in incised wounds of white rats, indicating its potential as a therapeutic agent in wound healing through anti-inflammatory mechanisms.